Comprehending Burnout in Nursing and Laboratory Professions: Frequency, Risk Factors, and Prevention Strategies - Bubshait, Zahrah Saleh Ahmad; Almushawwah, Qays Abdullah Mushawwah; Alsalamah, Fatimah Yousef; Alshabib, Ali Mohammed; Alghasham, Elyas Ameer; Al Harbi, Adel Saad; Al Salem, Salem Ibrahim; Alraqqas, Najla Musharri; Alqahtani, Muteb Awadh Abdullah; Al-Shmre, Ashwaq Al-Nashme; Alkhalaf, Ali Yaseen; Alahmary, Nawal Abdullah Saaed (Journal of Ecohumanism, 2024)
Burnout is a significant concern in healthcare professions, including nursing and laboratory fields, with profound effects on both individual well-being and the quality of patient care. This manuscript aims to explore the prevalence of burnout in these professions, examine the key risk factors that contribute to its development, and propose effective prevention strategies. A review of the current literature highlights that burnout is prevalent in both nursing and laboratory professions, with rates ranging from 30% to 70%, depending on various factors such as work environment, workload, and emotional labor. Risk factors identified include high patient-to-nurse ratios, emotional exhaustion, and lack of support. Effective prevention strategies, such as organizational interventions, professional development opportunities, and individual well-being practices, are critical in mitigating the negative consequences of burnout. This paper emphasizes the importance of addressing burnout at both the individual and systemic levels to foster a healthier and more sustainable healthcare workforce.